Analisis Linear Programming dengan Metode Simpleks untuk Memaksimalkan Keuntungan pada UD Sumberwaras di Karanganyar - Anissa Nur Azizah; Erni Widajanti (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2024)
This research is an analysis of maximizing profits at UD SUMBERWARAS using a simplex method linear programming analysis tool via the POM QM for Windows V5 application and carrying out manual calculations. The type of data used in this research is qualitative and quantitative data. The results obtained are H1 which states "The optimum amount of baby swaddle production at UD SUMBERWARAS produces 4,500 boxes of baby swaddles A, 4,000 boxes of baby swaddles B and 4,000 boxes of baby swaddles" and H2 which states "The maximum amount of profit obtained by UD SUMBERWARAS in Karanganyar amounting to Rp. 1,300,000,000” is not proven.